2017
DOI: 10.1177/1540796916684896
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the State of Affairs for Evidence-Based Practices in Students With Severe Disabilities

Abstract: The use of evidence-based practices (EBPs) was mandated with the passage of the No Child Left Behind Act of 2001 (NCLB), and continues with the Every Student Succeeds Act (ESSA). Accordingly, all children, including those with severe disabilities, must be taught both daily living and academic skills using EBPs. In this article, we synthesize, report, and establish the state of affairs for teaching EBPs to students with severe disabilities; examine established practices and considerations for the future of EBPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 33 publications
0
30
0
1
Order By: Relevance
“…Although many students in K through 12 classrooms can learn to function independently through incidental learning, others need formal, supported, and systematic instruction. Teaching students pivotal or functional skills need not exclude the opportunity to learn about academic science content and certainly not of science practices (Courtade et al, 2010; Spooner, McKissick, & Knight, 2017). It is unlikely that every student with ID or ID/ASD will enjoy learning the breadth of science content in their learning environments, but then, neither do students without disabilities.…”
Section: Resultsmentioning
confidence: 99%
“…Although many students in K through 12 classrooms can learn to function independently through incidental learning, others need formal, supported, and systematic instruction. Teaching students pivotal or functional skills need not exclude the opportunity to learn about academic science content and certainly not of science practices (Courtade et al, 2010; Spooner, McKissick, & Knight, 2017). It is unlikely that every student with ID or ID/ASD will enjoy learning the breadth of science content in their learning environments, but then, neither do students without disabilities.…”
Section: Resultsmentioning
confidence: 99%
“…This might be related to the nature of students with disabilities and their learning but is more likely a direct reflection of the preference of researchers in special education to favor behavioral approaches as their preferred theoretical framework. The dominant view in the special education field, therefore, is that explicit/systematic instruction is the most effective approach to teaching a range of new skills to students with disabilities (Spooner et al, ). The current review suggests teaching methods based on behavioral approaches are likely to be effective strategies for teaching science skills and knowledge to students with DDs.…”
Section: Discussionmentioning
confidence: 99%
“…Courtade et al () and Spooner et al () focused on students with severe ID only (IQ below 55), and Rizzo and Taylor () focused on all students with disabilities. Spooner, McKissick, and Knight () in their summative paper on evidence‐based practices for students with severe disabilities reported that at the time of the last comprehensive systematic review on teaching science to students with DD (Spooner et al, 2011), published studies were mainly focused on traditional functional curriculum domains (e.g., safety skills). Since then, more research targeting skills that are part of National Curriculum in the United Kingdom or NSES and the NGSS in the United States have been published.…”
Section: Previous Research On Science Education and Students With Devmentioning
confidence: 99%
“…The past decade of research has shown students with ESN can learn meaningful, grade-aligned academic skills (Courtade et al, 2014; Spooner, McKissick, & Knight, 2017), including in the area of mathematics (Spooner et al, 2019). In their review of mathematics research published between 2005 and 2017, Spooner and colleagues (2019) reported a shift toward supporting chronologically age-appropriate and grade-aligned skills rather than the traditional focus of “functional” mathematics and basic skills.…”
mentioning
confidence: 99%